Bonded amalgam as a fissure sealant in low-income setting: A randomised controlled trial - Farhan Raza Khan; Samreen Liaquat; Ghazala Rafique; Syed Iqbal Azam; Arshad Hasan (Journal of the Pakistan Medical Association, 2022)
Objective: To compare one year retention rate of bonded amalgam sealants (BAS) with that of conventional resinbased sealant (RBS). Methods: It was a parallel group, equivalence, randomised controlled trial done during March 2018 to December 2019 at the dental clinics of Dow University of Health Sciences, and the Jinnah Sind Medical University, Karachi, Pakistan on children aged 12-16 years, who were randomly assigned to one of the two treatment groups (BAS vs. RBS). Complete retention of the sealant at one year follow-up was labeled as success. Multi-level mixed effect logistic regression model was employed. Study was registered at www.clinicaltrials.gov # NCT NCT03130725. Results: There were 137 teeth (23 subjects) in the BAS and 128 teeth (15 subjects) in the RBS group that were evaluated for sealant retention at 12 months follow-up. Among the BAS group, 100/137 (73%) sealants were completely retained whereas 110/128 (86%) were fully retained in the RBS group. Nearly, 22/137 (16%) BAS and 10/128 (7.8%) RBS were completely dislodged. In multivariable analysis, subject age >15 years and male gender were found to be significantly associated with the dislodgement of sealants. Conclusions: At 12 months follow-up, the retention of bonded amalgam sealant (BAS) was significantly lower than that of the resin-based sealant (RBS). Keywords: Bonded amalgam sealants, Resin-based sealants, Retention, Caries. RCT Registration: www.clinicaltrials.gov with # NCT NCT03130725.